Analysis of 7 volatile N-nitrosamines in Chinese Sichuan salted vegetables by gas chromatography-tandem mass spectrometry coupled to modified QuEchERS extraction. (April 2019) - Zhang, Qixian; Jin, Lu; Zhang, Feng; Yao, Kai; Ren, Yao; Zhang, Jiaqi; Zhang, Qisheng; He, Qiang; Wan, Yuping; Chi, Yuanlong
Abstract: A gas chromatography-tandem mass spectrometry coupled to QuEchERS extraction method was developed for the determination of 7 volatile N -nitrosamines (VNAs) in Chinese Sichuan salted vegetables, and the method detection limit (MDL), method quantification limit (MQL), recovery and relative standard deviation (RSD) were determined. Furthermore, the VNA contents of 406 Sichuan salted vegetables were measured and discussed. The MDL of the 7 VNAs ranged from 0.02 to 0.15 ng/g, and their recoveies when spiked with 10 ng/g standards ranged from 91.5 to 106.1%. The within-day RSD and between-day RSD were 2.1–4.6% and 2.4–7.2%, respectively. These results indicate that the method developed was of good accuracy, repeatability and reproducibility. The mean content of total VNAs in the 406 Sichuan salted vegetables was 0.56 ng/g, and more than 95% of them (n = 386) were at low VNA content (<3 ng/g), which suggests good control of VNAs in Sichuan salted vegetables. Preparation method and packaging mode significantly affected the VNA content of Sichuan salted vegetables (P < 0.05), while vegetable type and production region did not (P > 0.05). The VNA with both the highest concentration and the highest occurrence frequency of ≥3 ng/g was N -nitrosopyrrolidine. Highlights: Seven VNAs of 406 Sichuan salted vegetables were determined by QuEChERS- GC-MS/MS. The developed method presented high sensitivity, precison and accuracy. Sichuan salted vegetables showed low levels of volatile N -nitrosamines. Preparation method and packaging mode significantly affected the VNA content. N -nitrosopyrrolidine was identified as the main VNA in Sichuan salted vegetables.